Description of Pregnant Women's Knowledge of the Importance of Implementing Pregnant Plan - Asdinar; Lestari, Aldina (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2017)
Based on the preliminary data collection at the Bontobangun Public Health Center, the number of pregnant women in 2014 was 462 people doing pregnancy exercises as many as 9.24 (9.24%), in 2015 there were 724 pregnant women doing pregnancy exercises. as many as 46 people (6.35%). The General Purpose of this Research is to know the Description of Pregnant Women Knowledge About the Importance of the Implementation of Pregnancy Gymnastics. Bulukumba in June 2016 The sampling technique used in this study was the accidental sampling technique. As for the population in this study were Pregnant women as many as 90 people and the sample in this study was pregnant women amounted to 47 people. As for the research instruments used in this study were questionnaires, and data collection techniques in this study were based on primary data and processed manually. From the research that has been done, the results show that from 47 respondents the knowledge of pregnant women about the importance of the implementation of pregnancy exercises are 3 people (6.4%) in the good category, 15 people (31.9%) in the sufficient category, and 29 people (61, 7%) in the less category. By looking at the results obtained, it can be put forward some suggestions as an effort to increase the knowledge of pregnant women about the importance of implementing pregnancy exercises, among others, for researchers it is expected that with this research, researchers can increase knowledge about the importance of implementing pregnancy exercises and can provide counseling and information in the future as the next generation. For institutions, it is expected to be able to add book references on pregnancy exercise, and for public health, it is expected that midwives can provide or improve counseling and information to pregnant women about the importance of implementing pregnancy exercises.